Convective heat transfer coefficient of apricots under open sun drying conditions - Togrul, IT (Taylor & Francis Ltd, 2005)
In this work, the convective heat transfer coefficients of apricots in open sun drying conditions were determined. Convective heat transfer coefficients were found at different initial moisture contents and at ambient temperature for apricots with various pretreatments. Convective heat transfer coefficient for apricots was found to increase exponentially with increasing moisture content. The coefficients of the exponential model were determined by using the Statistica program. To test the consistency of the models developed for apricots, some statistical tests were also used as well as correlation coefficients. The experimental error in terms of percent uncertainty was also calculated.
Keywords: apricot; heat transfer; solar energy; sun drying